Dialektika antara Mandat Prokreasi dan Eskatologi Perjanjian Baru dalam Menanggapi Fenomena Childfree - Adi Putra (Sekolah Tinggi Theologia Nazarene Indonesia, 2026)
This research examines the childfree phenomenon through the lens of the dialectic between the procreation mandate (Genesis 1:28) and New Testament eschatology. The aim is to redefine the concept of fertility to provide pastoral space for individuals who choose not to have offspring. Utilizing a qualitative-theological method with a biblical study approach, this research analyzes the transformation of the meaning of blessing and progeny within New Testament texts. The results indicate that in Christ, fertility has shifted from biological continuity to spiritual fertility through discipleship. Analysis of Ephesians 1, Matthew 19:12, and 1 Corinthians 7 confirms that spiritual blessings and the status as